Observational studies: practical tips for avoiding common statistical pitfalls - Anna Freni Sterrantino (Elsevier, 2024)
Summary: This Personal View is intended for early-career researchers who are not yet experts in statistics. The Personal View focuses on common but usually avoidable flaws in the context of observational studies. I point out how study design, data collection, and statistical methods impact statistical results and research conclusions. With particular attention to study planning, sample selection, biases, lack of transparency and results misinterpretations.